MOTOR IMAGERY TRAINING FOR MOTOR RECOVERY IN LEFT HEMIPARESIS POST-STROKE: A SHORT-TERM CASE STUDY - Taufiq, Isa; Septianingrum, Yurike; Soleha, Umdatus; Wijayanti, Lono (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2025)
Background: Stroke remains one of the leading causes of long-term disability worldwide, with hemiparesis being the most common motor deficit. Hemiparesis on the dominant side, such as sinistra hemiparesis, greatly impairs daily function. Motor Imagery Training (MIT) is a cognitive-based therapeutic approach that stimulates motor-related cortical areas through mental rehearsal of movement, offering a non-invasive, low-cost intervention to promote neuroplasticity during stroke rehabilitation. Objectives: This case study aims to evaluate the short-term effects of a 4-day Motor Imagery Training intervention on a post-stroke patient with hemiparesis sinistra, focusing on motor function improvement and cognitive engagement. Methods: Mrs SA, a 66-year-old female with a history of uncontrolled hypertension and prior stroke, presented with left-side weakness, facial asymmetry. The patient underwent MIT sessions for four consecutive days (30 minutes/day), guided by auditory scripts and visual imagery techniques targeting upper limb function. Motor performance was evaluated using the Fugl-Meyer Assessment for Upper Extremity (FMA-UE) and the Medical Research Council (MRC) scale. Results: After four MIT sessions, the patient demonstrated improved motor strength (MRC 4-/5), increased FMA-UE score from 29 to 36, and enhanced focus and engagement. Subjectively, the patient reported increased motivation and perceived movement initiation. These findings suggest early cortical activation and functional gains, even within a limited intervention period. Conclusion: This case supports existing evidence on the effectiveness of MIT in promoting neurofunctional recovery in stroke rehabilitation. Despite its brief duration, MIT contributed meaningfully to motor recovery and psychological readiness. Motor imagery is feasible for early rehabilitation and can be tailored to settings with limited resources.